2012
DOI: 10.1111/j.1438-8677.2012.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial genetic structure of aquatic bryophytes in a connected lake system

Abstract: Using genetic markers, we investigated the genetic structure of three clonal aquatic moss species, Calliergon megalophyllum Mikut., Fontinalis antipyretica Hedw. and F. hypnoides Hartm. on two scales: among populations in a connected lake system (large-scale spatial genetic structure) and among individuals within populations (fine-scale spatial genetic structure). Mean genetic diversities per population were 0.138, 0.247 and 0.271, respectively, and total diversities equalled 0.223, 0.385 and 0.421, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…Surprisingly, there was no eff ect at the smallest scale (1 km), even when the actual number of occurrences of the species in the surrounding area was used as the explanatory variable. However, as noted in the introduction several other studies on genetic structure and occurrence patterns suggest more restricted dispersal at a landscape scale (Sn ä ll et al 2004a, Hutsem é kers et al 2013, Korpelainen et al 2013, Rosengren et al 2013. Initially, this appears to be counterintuitive since we know that there is a steep decline in deposition of diaspores (also shown for spores) from a point source (S ö derstr ö m and Jonsson 1989, Bullock and Clarke 2000, Roads and Longton 2003, Sundberg 2005, L ö nnell et al 2012.…”
Section: Discussionmentioning
confidence: 90%
“…Surprisingly, there was no eff ect at the smallest scale (1 km), even when the actual number of occurrences of the species in the surrounding area was used as the explanatory variable. However, as noted in the introduction several other studies on genetic structure and occurrence patterns suggest more restricted dispersal at a landscape scale (Sn ä ll et al 2004a, Hutsem é kers et al 2013, Korpelainen et al 2013, Rosengren et al 2013. Initially, this appears to be counterintuitive since we know that there is a steep decline in deposition of diaspores (also shown for spores) from a point source (S ö derstr ö m and Jonsson 1989, Bullock and Clarke 2000, Roads and Longton 2003, Sundberg 2005, L ö nnell et al 2012.…”
Section: Discussionmentioning
confidence: 90%
“…From their study on the role of hydrochory (passive dispersal by water) on spatial genetic structure in the aquatic moss Rhynchostegium riparioides, Hutsemekérs et al (2013) concluded that shoot fragments rather than spores are involved in local dispersal and that the 'extremely limited routine dispersal' by these unspecialized diaspores, 'coupled with discrete episodes of population extinctions and colonizations by spores', account for the absence of a downstream increase in genetic diversity (which would be expected from downstream migration of propagules alone). Even in three purely clonal species (including F. antipyretica), where a downstream increase in genetic diversity should be expected, Korpelainen et al (2013) found no relationship between genetic similarity and distance after a few hundred meters and concluded that rare events of upstream dispersal of gametophyte fragments by waterfowls may take place, although they could not rule out completely a potential role of rare longdistance spore dispersal from areas where the species were fertile.…”
Section: Discussionmentioning
confidence: 91%
“…If F. antipyretica does produce the same array of vegetative diaspores in the wild as observed in vitro, this would add a new, important, dimension to any study of the dispersal capacity of F. antipyretica and how this might affect spatial patterns of genetic structure and diversity in this aquatic species. Hitherto, such studies on F. antipyretica and other aquatic mosses (Korpelainen et al, 2013;Hutsemekérs et al, 2013) have assumed that these plants are able to disperse by spores and/or unspecialized vegetative propagules i.e. shoot fragments only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clonal species can quickly resprout from dormant meristems after clone fragmentation, by reallocating resources stored in the stolons and rhizomes to the sites of new leaf and root production (Klimesova and Klimes 2007). Apart from the negative effects of flooding-induced disturbance, flooding may also play an important role as a long-distance dispersal agent (Korpelainen et al 2013). Clonal fragments may be spread along the riverine systems during flooding events, thereby allowing plants to invade new habitats or already established populations.…”
Section: Introductionmentioning
confidence: 99%